ANALISIS KORELASI USIA PESAWAT AIRBUS A320-200 TERHADAP JUMLAH KOROSI YANG TIMBUL MENGGUNAKAN METODE KORELASI PEARSON PRODUCT MOMENT - Reynaldo Mulya Tedja; Mufti Arifin; Erna Shevilia Agustian (Jurnal Teknologi Kedirgantaraan, 2023)
Corrosion is the destruction of materials caused by the environment, where metals separate from their metal atoms and form compounds from water or gas, resulting in oxidation until the metal atoms disappear. Corrosion can also be referred to as material that is damaged by the environment and is mostly caused by natural impacts that increase as the age of the aircraft increases. Failure to maintain the strength of the main structure is caused by excessive stress that occurs in the corrosion area resulting in cracks in the structure. Due to the frequent occurrence of corrosion in the aircraft, observations, data analysis and further literature studies were carried out. This study aims to determine the relationship between aircraft aging and the amount of corrosion found during periodic "c-check" servicing of Airbus A320-200 aircraft at the study site. The research method that used in the discussion of this thesis is to use pearson product moment correlation analysis on age data and the amount of corrosion that occurs on each aircraft. The conclusion of the results is analysis using the Pearson product moment method on 30 sample aircraft, the correlation 0.922 is categorized as having a very strong relationship. Each aircraft section does not have a strong correlation between corrosion and age, but as a whole has a strong correlation with age. From the results of the analysis using the linear regression equation, it can be identified and estimated the amount of corrosion that occurs at a certain age on the Airbus A320-200 aircraft. The results of the linear regression equation show that the aircraft is 23 years old, the amount of corrosion that will arise is estimated at 39 points, it can be concluded that aircraft with XU-029 registration are known to have a total corrosion rate of 42 points with poor corrosion conditions, then when compared to aircraft with registration XU-030 which is 23 years old is also known to have a corrosion rate of 30, so it can be concluded that the corrosion conditions on this aircraft are better than expected.